Toward the development of subnational hybrid input–output tables in a multiregional framework. (20th November 2020) - Towa, Edgar; Zeller, Vanessa; Merciai, Stefano; Schmidt, Jannick; Achten, Wouter M. J.
Abstract: Environmental input–output analyses can be a useful decision support tool at the subnational level, because of its ability to capture economic and environmental impacts at other geographical levels. Yet, such analyses are hindered by the lack of subnational IO tables. Furthermore, the lack of physical product and waste flows in what is known as a "hybrid" table prevents a range of consumption‐based and circular‐economy‐type analyses. We demonstrate the development of a multiregional hybrid IOT (MRHIOT) along with environmental extensions at the subnational level and exemplify it for the case of Belgium. The development procedure discloses a novel approach of combining national hybrid tables, subnational monetary tables, and physical survey‐based data. Such a combination builds upon a partial‐survey approach that includes a range of techniques for initial estimation and reconciliation within a balancing procedure. For the validation of the approaches, we assessed the magnitude of deviations between the initial and final estimates and analyzed the uncertainties inherent to each initial estimation procedure. Subsequently, we conducted a consumption‐based analysis where we assessed the carbon footprint (CF) at the subnational level and highlighted the CF inherent to the interregional linkages. This study provides methodological and application‐based contributions to the discussion on the relevance of hybrid subnational tables and analyses compared to national ones. The proposed approach could be replicable to some extent for further developing subnational MRHIOT. The study is expected to foster more research toward the development of further subnational MRHIOT as well as its associated wide‐ranging applications.